PENAMBAHAN BEBERAPA JENIS BAHAN NUTRISI PADA MEDIA PERBANYAKAN UNTUK MENINGKATKAN VIRULENSI BEAUVERIA BASSIANA TERHADAP HAMA WALANG SANGIT - Ni Siluh Putu Nuryanti; Lestari Wibowo; Abdul Azis (Universitas Lampung, 2012)
A research was conducted to increase the virulence of Beauvaria bassiana to the rice bug, L. acuta, by adding four different substances (materials) to the rice media to grow the fungus. The research was conducted from April to August 2011 at Polinela Laboratory, Bandar Lampung. To do this a set of experimental unit consisting of five treatments and five replications were arranged in completely randomized design. The four treatments were media made up of rice (rice based media) each given or added with four different materials such as rice skin powder, corn sugar, grasshopper powder and chitosan powder. The result showed that B. bassiana grown on rice media added with grasshopper powder or rice skin powder were able of causing mortality to the L. acuta as high as 78% and 71%, respectively, meaning that both mortalities were much higher than that of other replication. The virulence values of Beauveria bassiana grown on those both powder were also higher than that of three others.